EVALUASI PERFORMA BOBOT BADAN DAN STATISTIK VITAL SAPI MADURA BERDASARKAN TAHUN KELAHIRAN - Sulistyoningtyas I.; V.M. Ani Nurgiartiningsih; Gatot Ciptadi (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
This research was done to compare performance of Madura cattle born in 2015 and 2016 at Unit of Technical for Animal Breeding and Animal Health Madura. Two hundred tails of Madura cattle that were one day old, 205 days old, and 365 days old were used in this research. They were offsprings of 12 tails of male cattle and 200 tails of female cattle. Variables observed were body weight, body height, body length, and heart girth. Data collected were analyzed by t test. Result of this research indicated that performance of Madura cattle that was one day old and 205 days old born in 2015 and in 2016 were not different (P>0.05). Performance of Madura cattle that was 365 days old born in 2015 and in 2016 were different (P<0.05). The performance of cattle born in 2015 versus in 2016 were 113.00±12.19 kg vs 120.00±10.86 kg for body weight (yearling weight),  110.00±6.81 cm vs 114.00±2.46 cm for body height, 103.00±6.70 cm vs 106.00±4.71 cm for body length, and 118.00±8.05 cm vs 120.00±5.91 cm for heart girth. It could be concluded that performance of Madura cattle that was 365 days old born in 2016 were higher than that was in 2015. Keywords: Madura cattle, Body weight, Bidy height, Body length, Heart girth